Nutrition profile and rumen fermentation of Tithonia diversifolia fermented with Lactobacillus bulgaricus at different times and doses - Pazla, Roni; Jamarun, Novirman; Agustin, Fauzia; Arief, Arief; Elihasridas, Elihasridas; Ramaiyulis, Ramaiyulis; Yanti, Gusri; Ardani, Laily Rinda; Sucitra, Laras Sukma; Ikhlas, Zaitul (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This study aims to investigate the nutritional composition and rumen fermentation attributes of the tithonia plant (Tithonia diversifolia) treated with Lactobacillus bulgaricus bacteria at different fermentation durations and doses. Materials and Methods: In this research, an experimental approach employed a factorial pattern with two factors as treatments with three replications using a complete randomized design. The primary factor was the dose of L. bulgaricus inoculum, with concentrations at 2% and 3%. The secondary factor examined during the study revolved around the duration of fermentation, offering three time frames of 1 day, 3 days, and 5 days for analysis. The inoculum of L. bulgaricus contained 65 × 1015 CFU/ml. Results: The use of L. bulgaricus bacteria on tithonia plants (T. diversifolia) with different inoculum doses and fermentation times demonstrated a highly significant effect and significant disparities (p < 0.05). In phytic acid content, nutrient content (crude protein (CP), crude fiber, crude fat, and dry matter (DM)), and in vitro digestibility, which includes DM, organic matter (OM), CP, volatile fatty acids (VFA), NH3, and gas production. However, it did not show any significant interaction between pH and OM content. Conclusion: The optimal results of nutrient profiling and in vitro digestibility, including DM, OM, CP, rumen pH, VFA, NH3 (ammonia), and gas production, were observed when the tithonia plant (T. diversifolia) was fermented using L. bulgaricus with 3% inoculum doses and a fermentation time of 5 days. Adv. Vet. Anim. Res., 11(1): 146-152, March 2024 http://doi.org/10.5455/javar.2024.k759